Effect of Sustainable Marketing Activities on Customer Loyalty among Young Generations: Case of Fashion Industry in Greater Jakarta-Indonesia - Yusuf, Adzraa Shaafia Nur; Ferdy; Hendriana, Evelyn (Yayasan Sinergi Kawula Muda, 2024)
This research discusses the importance of sustainable marketing activities for the long-term success of companies. The research highlights the need for a multidimensional and systematic approach to understanding sustainable marketing by including the cultural dimension. Due to the lack of studies looking at the effect of four dimensions of sustainable marketing activities on customer loyalty, this study aims to test the effect of sustainable marketing activities on brand image, customer satisfaction, and customer loyalty. This research focuses on Generation Y and Z consumers in Greater Jakarta who are more concerned about sustainability issues and are aware of global fashion brands that have implemented ESG. Data from 218 samples selected using judgmental sampling were analyzed using PLS-SEM. The findings show that all dimensions of sustainable marketing activities significantly affect brand image, which sequentially influences customer satisfaction and loyalty. This study finds that cultural dimension has the greatest effect on brand image, while social dimension has the lowest effect. The positive brand image is found to increase customer satisfaction and loyalty. These findings confirm the application of signaling theory, and further practical implications are provided based on the findings.